A systematic review - Determinants of forward -Looking information disclosure by Malaysiancompanies / Judith Kristian Ah Choi... [et al.] - Ah Choi, Judith Kristian; Joseph, Corina (Universiti Teknologi MARA Cawangan Sarawak, 2020)
This paper focuses on the determinants of forward-looking information (FLI) disclosure in annual reports among the Malaysian public listed companies. FLI disclosure has gained prominent attention due to benefits it offered to various parties. This has attracted the interest of researchers for studies to be conducted on the determinants of FLI in annual reports. However, empirical evidence from previous studies failed to produce definite result. Therefore, this paper serves to examine the research pattern on determinants of FLI disclosure by reviewing the existing literatures. This study was guided by the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) and utilized two main databases known as Web of Science and Scopus. Consequently, nine relevant articles were retrieved which resulted in four categories of determinants (ownership structure, board of directors' characteristics, financial ratios, and other) under the internal factors and one category (auditors' type) under the external factor. The main categories produced another 17 sub-categories in total. Lastly, future researchers are recommended to conduct more studies by employing a approach and to adopt citation tracking to complement the current searching technique which is solely dependent on keywords search only.